Analysis of Time-to-Fatigue for Standing Jobs in Metal Stamping Industry - Isa, Halim (2011)
In metal stamping industry, almost all jobs are practically to be performed in standing position. Standing in a long period of time can lead to muscle fatigue. The objective of this study was to determine time-to-fatigue in the erector spinae, tibialis anterior, and gastrocnemius muscles of twenty production workers in a metal stamping company. The muscles activity was concurrently measured using surface electromyography (sEMG) during beginning, mid, and end of working sessions. Results of study found that gastrocnemius muscle fatigued earlier during all working sessions. In addition, working at the end of working session showed earlier fatigue than the beginning and mid of work days. The study concluded that standing in a long period of time is a cause to muscle fatigue experienced by the production workers.